2012
DOI: 10.1186/1746-1596-7-115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates and prognostic significance of SATB1 expression in colorectal cancer

Abstract: BackgroundSpecial AT-rich sequence-binding protein 1 (SATB1) is a global gene regulator that has been reported to confer malignant behavior and associate with poor prognosis in several cancer forms. SATB1 expression has been demonstrated to correlate with unfavourable tumour characteristics in rectal cancer, but its association with clinical outcome in colorectal cancer (CRC) remains unclear. In this study, we examined the prognostic impact of SATB1 expression in CRC, and its association with important molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 26 publications
4
84
3
Order By: Relevance
“…The Meng et al and Zhang et al studies observed a correlation of SATB1 protein expression with advanced disease stage and increased tumor depth of invasion [2,4]. However, both the Nodin et al and our study did not show any correlation indicative of a poorer disease outcome of SATB1 expression with patient characteristics [3]. There were also correlations with certain patient characteristics observed by one group but not seen by the other researchers, such as gender [3] and tumor differentiation grade [4].…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The Meng et al and Zhang et al studies observed a correlation of SATB1 protein expression with advanced disease stage and increased tumor depth of invasion [2,4]. However, both the Nodin et al and our study did not show any correlation indicative of a poorer disease outcome of SATB1 expression with patient characteristics [3]. There were also correlations with certain patient characteristics observed by one group but not seen by the other researchers, such as gender [3] and tumor differentiation grade [4].…”
Section: Discussioncontrasting
confidence: 54%
“…The SATB1 protein expression frequencies in CRC in these reports vary between 42% -59%. In normal colonic mucosa these frequencies varied between 3% -26% [2][3][4]. In our study, we observed a frequency of approximately 18% in cancerous tissues and a relatively high frequency of 52% in normal tissues.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations